2009
DOI: 10.1080/01926180802403302
|View full text |Cite
|
Sign up to set email alerts
|

Male Victims: The Nature and Meaning of Sexual Coercion

Abstract: In this qualitative study we interviewed twelve males who reported on the RELATE questionnaire that they were sexually coerced by their female partners. The purpose of these interviews was to understand more fully the nature and the meaning of their coercive experiences. Several themes became apparent for both the nature and meaning of sexual coercion. In the category of coercion, men reported experiencing three main modes of coercion: verbal, emotional, and blackmail. There were also three themes regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…This suggests that, contrary to expectations based on the traditional sexual script, most men do not dismiss their experiences of sexual coercion as trivial and do not experience them as positive and enjoyable anymore than the women do. This is in keeping with research that has shown that sexual coercion has a serious negative impact on some men and their relationships Platt & Busby, 2009). We adopted a broad definition of sexual coercion to capture responses to the full range of sexually coercive tactics (use of verbal coercion and/or physical force) and experiences (unwanted sexual fondling, oral sex, vaginal sex, and/or anal sex).…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that, contrary to expectations based on the traditional sexual script, most men do not dismiss their experiences of sexual coercion as trivial and do not experience them as positive and enjoyable anymore than the women do. This is in keeping with research that has shown that sexual coercion has a serious negative impact on some men and their relationships Platt & Busby, 2009). We adopted a broad definition of sexual coercion to capture responses to the full range of sexually coercive tactics (use of verbal coercion and/or physical force) and experiences (unwanted sexual fondling, oral sex, vaginal sex, and/or anal sex).…”
Section: Discussionmentioning
confidence: 98%
“…Such norms include the expectation that adolescent men should successfully manage what is regarded as playful sexual banter at work (Mosher & Tomkins, 1988 ; Sears et al, 2011 ; Stockdale et al, 1999 ). This pattern arose for DSB only – and did not extend to ASB – thus suggesting that internal maladjustment experienced by adolescent males experiencing DSB may have resulted from upsetting sexual behavior triggering personal questions about one’s own gender role and heterosexuality, and feelings of powerlessness and self-blame (Platt & Busby, 2009 ; Street, Gradus, Stafford, & Kelly, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on adolescents also suggested that their jealousy of sexual infidelity in dating relationships was a significant predictor of sexual abuse (Sesar, Pavela, Simic, Barisic, & Banai, 2012). Besides this, a partner might use sexual abuse as a tactic to control their partner; for example, the abusers might accuse and blame their partners for not loving them if they refuse to have sex (Platt & Busby, 2009).…”
Section: Discussionmentioning
confidence: 99%